Analisis Framing Terhadap Berita Pemilihan Gubernur Sumatera Selatan Tahun 2018 di Koran Sumatera Ekspres - Candra Kirana; Yulion Zalpa (Program Studi Politik Islam Universitas Islam Negeri Raden Fatah Palembang, 2020)
This paper will parse and explain the role of media in the Election of the Governor of South Sumatra in 2018. The media to be examined is the local media namely the Harian Sumatera Ekspres (Sumeks). Harian Sumeks is one of the media that dominates readers in south sumtra province. With such a position, of course, Sumeks has influence in building opinions in society. The theory used in this study is the framing theory of Zhongdan Pan and Gerald M.Kosicki models, This theory in analyzing data operationalizes the four structural dimensions of news teks as a framing device, namely syntax, script, thematic, and rhetorical. This research is a qualitative study using documents as the main data source. The results of this study indicate that Sumeks described the four participants of the South Sumtra Governor Election in 2018 as well. If at first galnce, it will be difficult to find out which candidate pairs are more inclined. However, when using framing theory, it can be seen that Sumeks tries to emphasize Dodi-Giri more than other pairs. In addition, it can be concluded that the way Sumeks displays each candidate get a good response from each candidate team because the framing that is built seems to favor all candidates so that this impacts on the number of incoming advertisements